INTERACTIVE LEARNING MEDIA SUBJECTS MATH ALGEBRA CASE STUDY SMP NEGERI 1 PARONGPONG - mamay syani; Seno Aji, Bagas; Ratna Juwita Sari, Deassy (Jurnal Sistem Informasi Galuh, 2023)
Education is a process of changing attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training efforts. Education plays an important role in the progress of a nation. Therefore, quality education is needed to advance a nation. Mathematics is one of the subjects that must be mastered in formal education. Mathematics is a basic science that has an important role in everyday life and in the development of science and technology. However, in reality a lot of students think mathematics is difficult because there are too many formulas that sometimes they don't know where the formulas come from. This has an impact on student motivation in learning mathematics is reduced. As a result, students' mathematics learning outcomes become unsatisfactory. UAT testing aims to evaluate user requirements (user requirements) carried out by 33 respondents consisting of students at SMP NEGERI 1 PARONGPONG. This test is carried out directly at the time of KBM with a questionnaire format distributed in leaflets. And got good results with a percentage of 80.4%.